Distance learning 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Distance learning'Spore keeps up morale,' writes Koffi Woglo from Tsevie in Togo, and he offers an idea worthy of follow-up. 'In our societies, there is a good level of awareness of agricultural issues and practices. I am sure that many people ask...